From the Margins to the Mainstream: Latino/a Theater in the U.S. - Jorge Huerta (Studies in 20th & 21st Century Literature, 2008)
The author discusses Latina/o theatre as it evolved from social protest theatre of the 1960s to professional theatre companies and theatre artists working throughout the country. Whereas there were few scholarly articles, no books about Latina/o theatre and no plays in print (in English) in 1970, today there is a wealth of material about the theatre of the three major Latina/o groups, Chicana/os, Cuban-Americans and (mainland) Puerto Ricans. Each of these groups has a distinct relationship to the United States, as expressed in their plays.
Keywords: Latino/a theatre; U.S.; social protest theatre; professional theatre; chicano/a; Cuban-Americans; Puerto Ricans